Individual differences in neural mechanisms of selective auditory attention in preschoolers from lower socioeconomic status backgrounds: an event‐related potentials study. Issue 6 (31st July 2015) - Isbell, Elif; Wray, Amanda Hampton; Neville, Helen J.
Abstract: Selective attention, the ability to enhance the processing of particular input while suppressing the information from other concurrent sources, has been postulated to be a foundational skill for learning and academic achievement. The neural mechanisms of this foundational ability are both vulnerable and enhanceable in children from lower socioeconomic status (SES) families. In the current study, we assessed individual differences in neural mechanisms of this malleable brain function in children from lower SES families. Specifically, we investigated the extent to which individual differences in neural mechanisms of selective auditory attention accounted for variability in nonverbal cognitive abilities in lower SES preschoolers. We recorded event‐related potentials (ERPs) during a dichotic listening task and administered nonverbal IQ tasks to 124 lower SES children (77 females) between the ages of 40 and 67 months. The attention effect, i.e., the difference in ERP mean amplitudes elicited by identical probes embedded in stories when attended versus unattended, was significantly correlated with nonverbal IQ scores. Larger, more positive attention effects over the anterior and central electrode locations were associated with superior nonverbal IQ performance. Our findings provide initial evidence for prominent individual differences in neural indices of selective attention in lower SES children. Furthermore, our results indicate a noteworthy relationship between neural mechanisms of selective attention and nonverbal IQ performance in lower SES preschoolers. These findings provide the basis for future research to identify the factors that contribute to such individual differences in neural mechanisms of selective attention. Abstract : To assess neural mechanisms of selective auditory attention, we recorded event‐related potentials (ERPs) during a dichotic listening paradigm from 124 preschoolers from lower SES backgrounds. We observed prominent individual differences in neural indices of selective attention. These individual differences were associated with nonverbal IQ performance. Children with more pronounced ERP attention effects, i.e., larger mean amplitude differences between the ERPs elicited by identical probes embedded in stories when attended versus unattended, had higher nonverbal IQ scores.